Treatment experiences of Latinas after diagnosis of breast cancer. Issue 16 (11th April 2017) - Katz, Steven J.; Wallner, Lauren P.; Abrahamse, Paul H.; Janz, Nancy K.; Martinez, Kathryn A.; Shumway, Dean A.; Hamilton, Ann S.; Ward, Kevin C.; Resnicow, Kenneth A.; Hawley, Sarah T.
Abstract : BACKGROUND: The authors examined racial/ethnic differences in patient perspectives regarding their breast cancer treatment experiences. METHODS: A weighted random sample of women newly diagnosed with breast cancer between 2013 and 2015 in Los Angeles County and Georgia were sent surveys 2 months after undergoing surgery (5080 women; 70% response rate). The analytic sample was limited to patients residing in Los Angeles County (2397 women). RESULTS: The pattern of visits with different specialists before surgery was found to be similar across racial/ethnic groups. Low acculturated Latinas (Latinas‐LA) were less likely to report high clinician communication quality for both surgeons and medical oncologists (<69% vs >72% for all other groups; P <.05). The percentage of patients who reported high satisfaction regarding how physicians worked together was similar across racial/ethnic groups. Latinas‐LA were more likely to have a low autonomy decision style (48% vs 24%‐50% for all other groups; P <.001) and were more likely to report receiving too much information versus other ethnic groups (20% vs <16% for other groups; P <.001). Patients who reported a low autonomy decision style were more likely to rate the amount of information they received for the surgery decision as "too much" (16% vs 9%; P <.001). CONCLUSIONS: There appears to be moderate disparity in breast cancer treatment communication and decision‐making experiences reported by Latinas‐LA versus other groups. The approach to treatment decision making by Latinas‐LA represents an important challenge to health care providers. Initiatives are needed to improve patient engagement in decision making and increase clinician awareness of these challenges in this patient population. Cancer 2017;123:3022–30. © 2017 American Cancer Society . Abstract : There is little disparity in breast cancer treatment communication and decision making experiences as reported by Latinas with low acculturation versus other groups. However, the approach taken by Latina patients with low acculturation with regard to treatment decision making represents an important challenge to health care providers.